Icariin inhibits the inflammation through down-regulating NF-κB/HIF-2α signal pathways in chondrocytes. Issue 11 (23rd November 2020) - Wang, Pengzhen; Meng, Qingqi; Wang, Wen; Zhang, Shaoheng; Xiong, Xifeng; Qin, Shengnan; Zhang, Jinli; Li, Aiguo; Liu, Zhihe
Abstract: Articular cartilage injury or defect is a common disease and is mainly characterized by cartilage degradation because of chondrocyte inflammation. By now, there are no effective drugs and methods to protect articular cartilage from degradation. Icariin (ICA) is a typical flavonoid compound extracted from Epimedii Folium with anti-inflammatory and bone-protective effects. Our previous studies demonstrate that ICA up-regulates HIF-1α expression and glycolysis in chondrocytes and maintains chondrocyte phenotype. As another member of HIFs family, HIF-2α always plays a key role in inflammation. The effect of ICA on HIF-2α is unclear by now. In the present study, we confirmed the findings in our previous study that ICA promoted not only chondrocyte vitality and extracellular matrix (ECM) synthesis, but also the anti-inflammatory effect of ICA. In bone defect mice, ICA inhibited the expressions of NF-κB and HIF-2α. In TNF-α-treated ADTC5 chondrocytes, ICA neutralized the activation of IKK (IKK phosphorylation), the phosphorylation of IkB and NF-κB and the expression of HIF-2α. Furthermore, ICA inhibited the nucleus transfer of NF-κB and the expressions of MMP9 and ADAMTS5, two key targets of NF-κB/HIF-2α signal pathway. Taken together, the present study demonstrated that ICA may increase the vitality of chondrocytes by suppressing the inflammatory injury through the inhibition on NF-κB/HIF-2α signaling pathway. ICA is one effective candidate drug for the treatment of articular cartilage injury.